2012
DOI: 10.1111/edt.12013
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of endodontically treated teeth with major hard tissue loss – bond strength of conventionally and adhesively luted fiber‐reinforced composite posts

Abstract: Luting system selection significantly influenced the bond strength of conventionally and adhesively luted FRCPs to bovine root canal dentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 59 publications
(89 reference statements)
0
20
0
2
Order By: Relevance
“…The placement of posts reduces the stress in the cervical area by directing along the post length the occlusion stress of the mouth [1,4,11,31]. Moreover, posts should be used when there is a need to provide additional retention for the core build-up [8,10,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The placement of posts reduces the stress in the cervical area by directing along the post length the occlusion stress of the mouth [1,4,11,31]. Moreover, posts should be used when there is a need to provide additional retention for the core build-up [8,10,13].…”
Section: Discussionmentioning
confidence: 99%
“…A prerequisite for the use of fiber posts is their adhesive cementation, which creates a bond between the post and the root canal dentin and form a structurally and mechanically homogeneous complex. The combination of an adhesive bond to the root canal dentin with a resin core build-up allows the restoration of nonvital teeth while preserving the remaining tooth structure [3,11,13]. However, the goal is not only to achieve a high retentive bond strength of the fiber post, but also to avoid any microbiologic leakage along the root canal or post and to avoid degradation of the fiber post structure [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the roots were sectioned using a double‐sided diamond disc (KG Sorensen, Barueri, SP, Brazil) and cleaved in the long axis to determine the fracture pattern after pull‐out testing. Then, the samples were analyzed using a stereomicroscope (Leica Microsystem, Wetzlar, Germany) at 40× magnification and classified according to the failure pattern in the cement–dentin interface into one of four types: adhesive (no cement on dentin surface); cohesive within the material (cement on dentin surface); cohesive within the substrate (failure in dentine); or mixed (association of adhesive and cohesive failures).…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16] Although posts are necessary to retain coronal build-up materials, they do not reinforce roots and may even weaken them through loss of radicular dentin necessitated by post space preparation, 6,17 while several studies also suggested that glass fiber posts contributed to the reinforcement and strengthening of endodontically treated teeth under full coverage crowns.…”
mentioning
confidence: 99%